COWPE BEAN PRODUCTION - (VIGNA UNGUICULATA (L.) WALP). A DROUGHT-RESISTANT PLANT IS VERY COMMON IN REGIONS OF THE BRAZILIAN SEMI-ARID - Rodrigues Maia, Felipe (Journal of Interdisciplinary Debates, 2023)
Cowpea is a dicotyledonous plant, originating from Africa, belonging to the order Fabales, Family Fabaceae, subfamily Faboideae, tribe Phaseoleae, subtribe Phaseolina, genus Vigna, species Vigna unguiculata (L.) Walp, the bean is considered a plant resistant to drought and is very common in regions of the Brazilian semi-arid region. It is commonly known as cowpea, macassar bean, black-eyed pea or green bean, among others. Given this, the objective of the present study was to carry out a bibliographical review of studies published in recent years to observe the nutritional potential and its economic viability for its production. The searches were carried out in Google Scholar databases. The harvested area of cowpea in the world is approximately 11,806,648 hectares, with a production of 5,389,235 tons, with Nigeria (2,916,00 tons) and Niger (1,265,839 tons) standing out among the largest producers. Cowpea production in Brazil is concentrated in the Northeast (1.2 million hectares) and North (55.8 thousand hectares) regions, predominantly cultivated in the semi-arid hinterland of the Northeast region, cowpea is cultivated in practically all micro-regions in the state of Paraíba, with a production of 62,018 tons in an area of 186,151 hectares, ranking fourth in planted area in the Northeast. The results show that cowpea has good energy and nutritional reserves that can be used in numerous recipes, including sautéed desserts, sweets, among others. Therefore, it presents itself as a very rich and nutritious food. A visit was made to some of Felipe Rodrigues Maia’s properties, in the rural community Sítio Cedro, with geographic coordinates of 37º57’20” longitude to the west and latitude to the south of 07º44’57”. It is located approximately four kilometers from the urban area of the municipality of Princesa Isabel - PB, to learn about the forms of production cultivation and the main pests that affect plantations in the semi-arid region and how to deal with this problem, as it is a factor Knowing its forms and how to deal with pests is crucial for cultivation. In view of what was obtained in the research, beans should be included in the human diet in a complementary way, considering that the crop is quite representative in the region where it plays an effective role in the population’s diet, as it constitutes an excellent source of low-cost proteins and carbohydrates.